2019
DOI: 10.1021/acsnano.9b03334
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control in Assembly of Plasmid DNA/Polycation Complex Nanoparticles

Abstract: Polyelectrolyte complex (PEC) nanoparticles assembled from plasmid DNA (pDNA) and polycations such as linear polyethylenimine (lPEI) represent a major nonviral delivery vehicle for gene therapy tested thus far. Efforts to control the size, shape, and surface properties of pDNA/polycation nanoparticles have been primarily focused on fine-tuning the molecular structures of the polycationic carriers and on assembly conditions such as medium polarity, pH, and temperature. However, reproducible production of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…Recently, it has been demonstrated that strong local shear stress generated by turbulence can promote the yield of platelet to enable clinical scale ex vivo manufacturing, which cannot be achieved in laminar flow [24] . The physico-chemical properties of nanocomposites and nanomedicine are also influenced dramatically by the competition between fluid dynamics and self-assembly performance [25] , [26] , [27] . With the help of ultrasound irradiation, Ag + could be reduced to AgNPs (around 8 nm) without using of any reductant and surfactant [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that strong local shear stress generated by turbulence can promote the yield of platelet to enable clinical scale ex vivo manufacturing, which cannot be achieved in laminar flow [24] . The physico-chemical properties of nanocomposites and nanomedicine are also influenced dramatically by the competition between fluid dynamics and self-assembly performance [25] , [26] , [27] . With the help of ultrasound irradiation, Ag + could be reduced to AgNPs (around 8 nm) without using of any reductant and surfactant [28] .…”
Section: Introductionmentioning
confidence: 99%
“…For in vivo experiments, nanoparticles comprised of the plasmid and l-PEI (in vivo-jetPEI, Polyplus Transfection, Illkirch, France) were prepared using the FNC process on a confined impinged jet (CIJ) device 14 , 16 . The CIJ device and all the fittings were autoclaved on a dry cycle prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled by a digital syringe pump, the solutions were then steadily injected into the CIJ device at a flow rate of 20 mL/min. The turbulent mixing in the CIJ device allowed a superfast mixing of the materials, thus enabling controlled nanoparticle assembly kinetics that resulted in a controlled nanoparticle size and composition 14 . The production is an operator-independent process 16 that generated large quantities of nanoparticles with the same properties across different batches of studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst BPEI contains various primary, secondary, and tertiary amines, LPEI displays only secondary amines [ 11 , 13 ]. PEI is known for its high cationic charge density [ 14 ] enabling efficient condensation of nucleic acids via electrostatic interactions [ 10 , 15 , 16 , 17 ]. Most importantly, the high availability of amine groups of PEI displays a large buffering potential at physiological pH [ 14 ].…”
Section: Introductionmentioning
confidence: 99%